Auricular Acupressure Effectively Reduces Labor Anxiety in Primigravidae by Increasing β-Endorphin Levels - Setiawandari, Setiawandari; Saputra, Koosnadi; Waroh, Yuni Khoirul; Andarwulan, Setiana (Folia Medica Indonesiana, 2023)
Highlights: 1. Auricular acupressure at the Shenmen point is effective in reducing anxiety. 2. Auricular acupressure is more practical than body acupressure since it does not interfere with expectant mothers' mobilization. 3. As a non-pharmacological method, auricular acupressure is cost-effective, efficient, and effective in overcoming maternal anxiety during labor Abstract Anxiety is a common psychological symptom in expectant mothers, particularly among primigravidae during labor. There is a link between excessive anxiety and prolonged labor. One of the options to manage anxiety is the use of non-pharmacological methods. Numerous studies have investigated the effectiveness of auricular acupressure to treat anxiety, but few have examined its effect on anxiety biomarkers. Thus, the objective of this study was to analyze the effect of auricular acupressure targeting the Shenmen point on the levels of β-endorphins and anxiety among primigravidae during the first stage of labor. This experimental study used a pretest-posttest control group design. The research subjects were primigravidae in the first stage of labor at the independent midwife practice of Yefi Marliandiani in Surabaya, Indonesia. Among 40 primigravidae, 34 individuals met the inclusion criteria and were then equally divided into treatment and control groups using a simple randomization. The treatment group received auricular acupressure at the Shenmen point every 30 minutes for a duration of 5 minutes, while the control group practiced deep breathing relaxation. The anxiety levels were assessed using the Hamilton Anxiety Rating Scale. The β-endorphin levels were measured by drawing 3 cc of venous blood before (4 cm cervix dilation) and after (9–10 cm cervix dilation) treatment. The obtained data were analyzed using paired- and independent-samples t-tests. A decrease in the mean anxiety level was observed in the treatment group (18.59±7.52) relative to the control group (19.76±7.11), albeit not significant (p=0.64). Simultaneously, the average β-endorphin levels of the treatment group (355.4±224.7) increased compared to the control group (225.1±127.5), with a significant difference observed between the two groups (p=0.04). In conclusion, while both auricular acupressure at the Shenmen point and deep breathing relaxation are effective in reducing anxiety, the former is more prominent in its ability to increase β-endorphin levels.